Chemosensitivity-directed therapy compared to dacarbazine in chemo-naive advanced metastatic melanoma: a multicenter randomized phase-3 DeCOG trial - Ugurel, Selma; Schadendorf, Dirk; Utikal, Jochen (OncoTarget, 2017)
Chemotherapy still plays an important role in metastatic melanoma, particularly for patients who are not suitable or have no access to highly efficacious new therapies. Pre-therapeutic chemosensitivity testing might be useful to identify optimal chemotherapy regimens for individual patients. This multicenter randomized phase-3 trial was aimed to test for superiority of chemosensitivity-directed combination chemotherapy compared to standard dacarbazine monochemotherapy, and to demonstrate the chemosensitivity test result as prognostic in metastatic melanoma. Chemo-naive patients with advanced melanoma were biopsied from metastatic lesions. Tumor cells were isolated and tested ex-vivo for sensitivity to chemotherapeutic agents using an ATP-based viability assay. Patients with evaluable test results were randomly assigned to receive either chemosensitivity-directed combination chemotherapy (paclitaxel+cisplatin, treosulfan+gemcitabine, treosulfan+cytarabine), or dacarbazine. The primary study endpoint was overall survival (OS). After inclusion of 287 patients and a median follow-up of 26 months, the per-protocol population (n=244) showed no difference in OS between chemosensitivity-directed therapy and dacarbazine (median 9.2 vs 9.0 months, HR=1.08, p=0.64). The disease control rate (CR+PR+SD) tended to be higher in patients treated with chemosensitivity-directed therapy (32.8% vs 23.0%, p=0.088); objective response rates (CR+PR) showed no difference between groups (10.7% vs 12.3%, p=0.90). Patients whose tumors were tested chemosensitive showed no better OS or response rate than patients with chemoresistant tumors. Severe toxicities (CTC grade 3-4) were significantly more frequently observed with chemosensitivity-directed combination chemotherapy than with dacarbazine (40.2% vs 12.3%, p<0.0001). These results indicate, that chemosensitivity-directed combination chemotherapy is not superior to dacarbazine, but leads to significantly more severe toxicities.
Gesehen am 08.10.2018